(untitled) (International Seven Journal of Multidisciplinary, 2025)
Oncologic pain is one of the most prevalent symptoms in patients with cancer and represents a significant challenge for the healthcare team, especially for nurses, who play a fundamental role in managing and relieving this suffering. Historically, the treatment of oncologic pain has been based on pharmacological approaches, such as the use of opioids, which, although effective, present limitations and important side effects. However, non-pharmacological practices have emerged as effective alternatives for pain control, providing relief from physical and emotional distress. The present study aims to analyze the applicability of non-pharmacological measures in relieving pain in oncology patients, highlighting the effectiveness of these practices and the role of nursing professionals in this process. This is an integrative literature review that included articles published in the last five years in databases such as PubMed, SciELO, and LILACS. The study emphasized that non-pharmacological interventions, such as music therapy, phytotherapy, and kinesiotherapy, are effective strategies for improving patients’ quality of life, reducing symptoms such as fatigue and insomnia. However, adherence to these practices is still limited, mainly due to the lack of knowledge and training among healthcare professionals. Moreover, the underuse of opioids remains a challenge in pain management, often due to patients’ and families’ fear regarding dependence and adverse effects. This resistance reinforces the need for health education to demystify the use of these medications and promote more effective pain control. The study also highlights the importance of multidisciplinary and individualized care, considering the particularities of each patient. Integration among nursing staff, physicians, and mental health professionals can optimize treatment, ensuring more humane care focused on patient well-being. It is concluded that the implementation of non-pharmacological interventions, along with public policies that encourage professional training, can significantly contribute to the control of oncologic pain. Investment in education, research, and integrated care is essential to provide more effective treatment, reducing patients’ suffering and promoting better quality of life.